The mainstream media view of the Fintech Revolution (Intercom - Brazilian Journal of Communication Sciences, 2023)
International mainstream media have presented fintech as revolutionary and a threat to the traditional banking industry. This article explores how that image is constructed. Designed to expand access to the banking system, fintechs should follow social responsibility parameters and fill a market gap left by banks. We chose to analyze the media for its character as a barometer of perception and understanding of specific logics (LOK, 2010). We analyzed articles from the New York Times and the Financial Times for 24 months. The articles showed that the media, when dealing with fintech, uses expressions such as “threat”, “competition”, “disruption”, “revolution,” and, with much less emphasis, social consequences. Our analysis found an ambiguous discourse of market rationalization in an attempt to align practices with Corporate Social Responsibility (CSR) in an industry under construction.
Keywords: Fintech; Financial Sector; Technology; Media; CSR